Penentuan Dosis Optimum Pemupukan N, P, dan K pada Tanaman Kacang Bogor [Vigna subterranea (L.) Verdcourt] - Lestari, Sri Ayu Dwi Ayu Dwi; Melati, Maya; Purnamawati, Heni (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTBambara groundnut is considered tolerant to drought and unfertile soil; therefore, has higher potential to be cultivated. The average yield of dry pod weight from agricultural fields in Indonesia is still low (< 4 ton ha-1); hence, the cultivation technique must be improved. Fertilizer is the main input to increase yield of Bambara groundnut, but the optimum rates of N, P, and K have not been determined. Therefore, the objectives of the research were to determine the optimum rate of N, P, and K fertilizer for Bambara groundnut production. Three parallel experiments were conducted at Cikarawang Experimental State, Dramaga, Bogor from March to July 2013. Each experiment tested different rates of N or P or K fertilizer with compeletely randomized block design and three replications. The fertilizer rates were 0, 50, 100, 150, and 200% of recommendation rate (100% N = 100 kg Urea ha-1, 100% P = 150 kg SP-36 ha-1, 100% K = 75 kg KCl ha-1). The results showed that leaf P content increased linearly with N fertilizer application. Leaf N content linearly decreased with P fertilizer application. Leaf P content and shoot dry weight quadratically increased with K fertilizer application. The optimum rates of N and P fertilizer was unable to be determined due to insignificant response of several variables. Optimum rate of K fertilizer ranged 86.4-118.95 kg KCl ha-1.Keywords: leaf nutrients, multi nutrient response, recommendation rate